Dissecting aortic aneurysm type A: The results of long-term opytalecheniya - I. M. Kravchenko; V. I. Kravchenko; I. A. Osadovska; O. B. Larioniva; O. A. Tretyak; V. A. Lytvynenko; V. E. Duplyakina; O. V. Pantas; Yu. M. Tarasenko (Ukrainian Journal of Cardiovascular Surgery, 2016)
Surgical treatment of dissecting aortic aneurysm type A remains one of the most difficult problems of cardiovascular surgery. The article served the whole experience of surgical treatment of aneurysms with one team. It is shown that the accumulation of experience, improve surgical techniques, brain protection, the heart, internal organs allowed is achieved in-hospital mortality of 4.5% over the past 5 years.